2016
DOI: 10.1177/2326409816669027
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Inborn Errors of Metabolism by Expanded Newborn Screening in a Mexican Hospital

Abstract: Newborn screening for the detection of inborn errors of metabolism (IEM), endocrinopathies, hemoglobinopathies, and other disorders is a public health initiative aimed at identifying specific diseases in a timely manner. Mexico initiated newborn screening in 1973, but the national incidence of this group of diseases is unknown or uncertain due to the lack of large sample sizes of expanded newborn screening (ENS) programs and lack of related publications. The incidence of a specific group of IEM, endocrinopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…NBS in Mexico was one of the earlier NBS programs in LATAM, beginning in 1973 but paused from 1977 until 1986. In 1988, NBS for CH was formalized by rule [ 1231 ]. Currently, the National Center for Gender Equity and Reproductive Health within the MOH is responsible for NBS policies and the screening panel includes CH, CAH, PKU, GALT, CF, and G6PD [ 1232 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NBS in Mexico was one of the earlier NBS programs in LATAM, beginning in 1973 but paused from 1977 until 1986. In 1988, NBS for CH was formalized by rule [ 1231 ]. Currently, the National Center for Gender Equity and Reproductive Health within the MOH is responsible for NBS policies and the screening panel includes CH, CAH, PKU, GALT, CF, and G6PD [ 1232 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are three different healthcare providers in Mexico that serve the population according to employment-based social insurance, uninsured public assistance, and private employer’s insurance [ 1227 , 1233 ]. Different screening approaches occur in the various hospitals, groups of hospitals, and government departments without any unified central coordination [ 1231 , 1234 , 1235 , 1236 ]. The Secretary of Health oversees the highest percentage coverage of Mexican newborns [ 1237 , 1238 ].…”
Section: Resultsmentioning
confidence: 99%
“…The birth prevalence of PA across Asia-Pacific, Europe, and North America is 0.29, 0.33, and 0.33 per 100000 newborns, respectively[ 7 ], however, it is still unknown in Mexico. This disorder appears to be very rare for the Mexican population, as determined by at least two expanded neonatal screening reports applying an acylcarnitine profile[ 8 , 9 ], even though PA comprises around 7% of all detected inborn errors of intermediary metabolism in Mexican patients[ 10 ]. To date, in the Human Gene Mutation Database ( ), there are around 25 splicing defects responsible for PA. To the best of our knowledge, the c.2041-1G>T variant has not been reported in the literature as associated with PA.…”
Section: Discussionmentioning
confidence: 99%
“…16 In another study Sharma et al also documented G6PD deficiency as the most prevalent disorder but contrary to our findings they reported a very high incidence of 44% of the total diagnosed cases. 17 Cantu´-Reyna et al found G6PD deficiency and hemoglobinopathies as the most frequent disorders. 18 Echeverri et al screened different IDM and listed aminoacidopathies as the commonest disorders followed by organic aciduria and Lysosomal storage disorders.…”
Section: Discussionmentioning
confidence: 99%